1999
DOI: 10.1042/0264-6021:3440109
|View full text |Cite
|
Sign up to set email alerts
|

Formation of glyoxal, methylglyoxal and 3-deoxyglucosone in the glycation of proteins by glucose

Abstract: The glycation of proteins by glucose has been linked to the development of diabetic complications and other diseases. Early glycation is thought to involve the reaction of glucose with N-terminal and lysyl side chain amino groups to form Schiff's base and fructosamine adducts. The formation of the alpha-oxoaldehydes, glyoxal, methylglyoxal and 3-deoxyglucosone, in early glycation was investigated. Glucose (50 mM) degraded slowly at pH 7.4 and 37 degrees C to form glyoxal, methylglyoxal and 3-deoxyglucosone thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
349
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(355 citation statements)
references
References 30 publications
2
349
0
4
Order By: Relevance
“…Some AGE, such as N ɛ -carboxymethyl-and N ɛ -carboxyethyl-lysines and pentosidine, accumulate with age on tissue proteins, and at an increased rate in LDL and atherosclerotic lesions from patients with diabetes [16,[18][19][20]. N ɛ -Carboxymethyllysine and N ɛ -carboxyethyllysine are formed on reaction of Lys residues with low-molecular-mass aldehydes (glyoxal/glycolaldehyde and methylglyoxal, respectively) arising from glucose and metabolic pathways [21], providing evidence for a role of such aldehydes in diabetes-induced complications. These aldehydes are present at elevated levels in the plasma of patients with diabetes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Some AGE, such as N ɛ -carboxymethyl-and N ɛ -carboxyethyl-lysines and pentosidine, accumulate with age on tissue proteins, and at an increased rate in LDL and atherosclerotic lesions from patients with diabetes [16,[18][19][20]. N ɛ -Carboxymethyllysine and N ɛ -carboxyethyllysine are formed on reaction of Lys residues with low-molecular-mass aldehydes (glyoxal/glycolaldehyde and methylglyoxal, respectively) arising from glucose and metabolic pathways [21], providing evidence for a role of such aldehydes in diabetes-induced complications. These aldehydes are present at elevated levels in the plasma of patients with diabetes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple sources and mechanisms in the formation of AGEs in vivo, involving both oxidative and nonoxidative reactions of reducing carbohydrates and other metabolic intermediates with amino acid residues (28). The AGE precursor 3DG, which is increased in patients with diabetes (29), is formed by nonoxidative modifications of Amadori adducts and from fructose-3-phosphate (30). In line with these observations, we found that 3DG increased more after the carbohydrate-rich meals than after the fat-rich meals.…”
Section: Figure 2-relations Between Postprandial Changes Of the Oxidimentioning
confidence: 99%
“…Alterations in the functions of two glycolytic enzymes, triose phosphate isomerase (TIM) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which control the levels of GAP and DHAP may lead to the accumulation of DHAP ( Figure 1) and cause an increase in cellular MG concentration [18,19]. Lower quantities of MG are formed from the decomposition of Amadori products of the autooxidation of free monosugars, or from the oxidation of acetone as well as from L-threonine via aminoacetone [20][21][22]. The level of cellular AGE depends on the intracellular mechanisms of enzymatic MG detoxification in the glyoxalase or aldose reductase system, as well as on the activity of fructosamine-3-kinase and fructoselysine-3-phosphate hydrolase, the enzymes which releases free hexose from proteins glycated at early steps of the Maillard reaction [23,24].…”
Section: Introductionmentioning
confidence: 99%